IMPACT OF COAL PROPER ASSESSMENT AND FOLLOW-UP SUPPORTING SUSTAINABLE DEVELOPMENT AT PT. CAHAYA ENERGY MANDIRI - Suryaningsi Suryaningsi; Mohammad Bahzar; Jawatir Pardosi (Educational Studies: Conference Series, 2021)
Development environmental insight is carried out consciously and planned, especially the management of mineral and coal resources to improve the quality of human life. The purpose of the study was to determine the response of PT. Cahaya Energi Mandiri on the impact and follow-up on the performance of mining companies to support sustainable development. This research is a qualitative descriptive study using an empirical legal design. The research location is PT Cahaya Energi Mandiri. The types of data used include primary data, secondary data and tertiary data. The data technique used in interviews and literature study. Data analysis used an interactive analysis model. The research findings are 1) The impact of the mining company's performance appraisal is very helpfulfor the company to always apply environmental care and improve environmental management. The mine reclamation/closure program takes into account the inputs/needs of the community around the mine. 2) Follow-up efforts for the company by complying with government directives, implementing the recommendations of applicable regulations, including when the company encounters problems in following up, the government is always ready, caring, and open to give directions without delay. The conclusion is that the impact of the mining company's performance assessment is effective and able to increase the compliance of the company's management in maintaining and being responsible for environmental management. Since 2019 the Company has not operated so that in 2021 there will be no visits from the mining company's performance. So that in 2020 the company only won the title of "Red Flag". However, the Company is always committed to complying with the mining company's performance appraisal criteria.